2008
DOI: 10.4319/lo.2008.53.6.2754
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and burial of carbon from settling cyanobacterial blooms by deposit‐feeding macrofauna

Abstract: Abstract-Summer blooms of filamentous, nitrogenfixing cyanobacteria are typical of the Baltic Sea, and recent findings indicate that cyanobacteria may be an important food source for the benthos below the euphotic zone. In a 2-week laboratory experiment, we measured incorporation of cyanobacterial carbon by the depositfeeding amphipod Monoporeia affinis when exposed to 14 Cradiolabeled, natural blooms of cyanobacteria dominated by either the toxic Nodularia spumigena or nontoxic Aphanizomenon sp. Carbon from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…This OM had a molar C/N ratio of 5.2, similar to that of Aphanizomenon sp. (C/N=4.9; Karlson et al, 2008). Such C/N ratio was lower than other sources of organic matter used in previous studies (Caffrey et al, 1993;Conley and Johnstone, 1995;Holmer, 1996), which were 7.5, 7.2 and 7.6 for yeast, diatoms and flagellates, respectively.…”
Section: Reconstructed Sediment Characteristicscontrasting
confidence: 50%
“…This OM had a molar C/N ratio of 5.2, similar to that of Aphanizomenon sp. (C/N=4.9; Karlson et al, 2008). Such C/N ratio was lower than other sources of organic matter used in previous studies (Caffrey et al, 1993;Conley and Johnstone, 1995;Holmer, 1996), which were 7.5, 7.2 and 7.6 for yeast, diatoms and flagellates, respectively.…”
Section: Reconstructed Sediment Characteristicscontrasting
confidence: 50%
“…We did not include a P. femorata þ M. balthica treatment since this combination is hardly found in nature. Even though earlier studies found no negative effects in benthic infauna that fed on N. spumigena (Karlson et al 2008), we also included treatments corresponding to Ma, Pf, Mb, and Ma þ Pf þ Mb (n ¼ 4) to which no cyanobacterial bloom material was added. These were intended as controls for the cyanobacterial addition, not for the biodiversity effects.…”
Section: Experimental Designmentioning
confidence: 99%
“…Decomposed CBB can be an important benthic food source [4] and decomposition products can be assimilated by rooted macrophytes [5]. As CBB undergoes decomposition, both nitrogen and phosphorus containing compounds are released.…”
Section: Introductionmentioning
confidence: 99%